The Effectiveness of Restorative Justice in Judicial Decisions: The Transformation of the Sentencing Paradigm in Indonesia - Alif Fajar Herihanli Palimai; Mulyati Pawennei; Baharuddin Badaru (Al-Ishlah: Jurnal Ilmiah Hukum, 2026)
This study examines the effectiveness of implementing restorative justice within Indonesia’s sentencing system in light of recent criminal law reform. Restorative justice, which emphasizes victim recovery, offender accountability, and social reconciliation, reflects values long embedded in Indonesia’s customary traditions. The enactment of Law Number 1 of 2023 concerning the Criminal Code marks a significant normative and philosophical shift from retributive punishment toward restoration and social balance. Despite the availability of various regulatory frameworks and institutional guidelines, challenges remain, particularly in procedural law, regulatory fragmentation, limited institutional capacity, and prevailing retributive legal culture. Using a normative juridical approach supported by conceptual and statutory analysis, this research evaluates the consistency between restorative justice principles and their practical application in judicial decisions. The findings indicate that restorative justice in Indonesia is in a transitional phase, with stronger implementation in juvenile and minor offense cases, while broader application still requires harmonization of criminal procedure law, enhanced judicial capacity, and systemic coordination among law enforcement agencies. Strengthening these aspects is essential to ensure that restorative justice becomes a substantive and consistent paradigm within Indonesia’s modern sentencing system.